Does the Emission Trading Scheme achieve the dual dividend of reducing pollution and improving energy efficiency? Micro evidence from China. (1st December 2022) - Du, Zhili; Xu, Chongchong; Lin, Boqiang
Abstract: Resolving the negative externality of environmental pollution has always been a concern in both the theoretical and practical space. To stimulate enterprises to participate in environmental governance actively, China has implemented a series of environmental regulation policies. The Emission Trading Pilot Scheme (ETPS) is an example of such policies implemented to ensure the gradual transition toward marketization. From a micro-enterprise perspective, the study examines how this policy achieves the dual effects of reducing emissions and promoting energy efficiency. We further explore potential channels through which this policy influences the dual effects. We empirically find ETPS to reduce the pollution emissions of enterprises significantly. However, the pollution reduction effect is mainly achieved by encouraging enterprises to strengthen cleaner production rather than through end governance. In addition to bringing environmental dividends, we observe ETPS to improve fossil energy efficiency by about 7.5% indirectly. We conclude by urging policy makers and participants to optimize energy structures and adjust intermediate input as they serve as significant pathways through which ETPS can affect fossil energy efficiency. The ETPS can encourage enterprises to actively step out of their "comfort zone" of environmental governance to be viewed as an effective environmental regulation policy. Highlights: The micro impact of Emission Trading Pilot Scheme (ETPS) is assessed. The ETPS achieves environmental dividends by promoting cleaner production. The ETPS significantly improves fossil energy efficiency by about 7.5%. Energy structure and intermediate input are channels to boost energy efficiency.